STUDI PENGEMBANGAN EKONOMI LOKAL TERKAIT INTERAKSI DESA-KOTA - HARIAYANTO, ASEP (Program Studi Perencanaan Wilayah Kota, 2014)
Study of Local Economic Development (LED) in Banjar district is determined from the determination Spatial Plans (RTRW) Banjar district regarding domestic Airguci handicraft industry which is in East Martapura Sub-district, precisely in the Mekar Village and the Melayu Ulu Village. This study starts from the initial assumption that there is no balance in the construction planning for urban and rural areas. The purpose of this study are: first, to develop the local economy Airguci craft based on the potential problems, opportunities and threats in order to improve the economy of rural communities, both improving the relationship of mutual support (interaction) between villages and cities in an effort to reduce the inequality between regions. The research method uses a combination of approaches, methods of qualitative and quantitative methods. Source of data derived from primary and secondary survey. Data collection techniques performed through questionnaires, interviews, observation and documentation. Data were analyzed using analysis of Diamond Porter, SWOT analysis, and analysis of the gravity of the rural-urban interactions. The results showed that the implementation of LED in the Airguci centers undeveloped and still is as a sideline activity. People especially women are actively involved in this business activity. But unfortunately, see the existing condition in the Airguci centers are not supported by good infrastructure such as roads and institutions that have not been running for the establishment of a business group that Airguci craft business activities can continue to survive. So many women who have been married, moved to the outside of the village. There are still many who choose to work in the city. Factors to be driving at the same obstacle in the implementation of the LED Airguci centers include: human resources, capital, marketing and institutional. The economic impact of the implementation of the LED in the Airguci centers, namely the local communities to help increase revenue and reduction in unemployment has not yet arrived when the harvest season.